Prevalence of heart disease in dogs was very high and required early diagnosis through physical examination, electrocardiogram, and echocardiography. Normal reference values of echocardiography are highly breedspecific and need for comparison and evaluation of dogs suspected with heart disease. Therefore the aim of this study was to establish normal reference echocardiographic values for Indonesian mongrel dogs, specifically to find out intracardiac dimensions, wall thickness, and fractional sho - DENI NOVIANA; DEVI PARAMITHA; RETNO WULANSARI (HAYATI Journal of Biosciences, 2011)
Prevalence of heart disease in dogs was very high and required early diagnosis through physical examination, electrocardiogram, and echocardiography. Normal reference values of echocardiography are highly breedspecific and need for comparison and evaluation of dogs suspected with heart disease. Therefore the aim of this study was to establish normal reference echocardiographic values for Indonesian mongrel dogs, specifically to find out intracardiac dimensions, wall thickness, and fractional shortening. Motion-mode and two-dimensional echocardiography from right parasternal short axis and long axis view were performed on nine clinically healthy dogs consisting of five males and four males. The results showed that wall thickness and fractional shortening of Indonesia mongrel dogs were higher compared with those in the other breed that have the same average weight. As opposite, the intracardiac dimensions and lumen dimensions of aorta and left atrial diameter were smaller. These differences might occur due to factors other than the dog’s habits and functions such as working and hunting, but can also be caused by the existence of breed differences. There was no significant difference between male and female dogs in terms of intracardiac dimension systole (P = 0.53), diastole (P = 0.38), fractional shortening (P = 0.053), and the ratio of aorta and left atrial diameter (P = 0.06).